Reproduksi Realitas: Mimesis dalam Antologi Puisi Lupakan Payung dan Biarkan Hujan Karya Hasan Aspahani - Zikri Zul Arvi; Nur Avida, Martina; Cahyani, Intan; Aleksa, Afrila; Elmustian, Elmustian (J-SES : Journal of Science, Education and Studies, 2025)
This study examines the representation of reality in the poetry antholog "Lupakan Payung dan Biarkan Hujan" by Hasan Aspahani using mimetic approach. The purpose of the study was to identify and analyze how the poems in the anthology represent the social, cultural, and psychological realities of Indonesian society in 2021. The method used is descriptive qualitative with library study techniques through repeated reading, data identification, and meaning analysis. The results showed that the poems of Hasan Aspahani can be grouped into five patterns of mimetic representation, namely: (1) attachment to identity in space and place, (2) alienation in urban life, (3) inner reflection through natural elements, (4) exploration of creativity and the power of language, and (5) inner wounds and healing processes. This study concludes that the anthology of poetry by Hasan Aspahani serves as a sharp mirror to the complexity of contemporary Indonesian society, showing that the mimetic approach remains relevant for studying modern Indonesian poetry that represents reality in rich detail, both from the geographical-cultural, socio-economic, and psychological-existential dimensions.